Effects of Age and Size on Xylem Phenology in Two Conifers of Northwestern China - Zeng, Qiao; Rossi, Sergio; Yang, Bao (Frontiers in Plant Science, 2018)
The climatic signals that directly affect the trees can be registered by xylem during its growth. If the timings and duration of xylem formation change, xylogenesis can occur under different environmental conditions and subsequently be subject to different climatic signals. An experimental design was applied in the field to disentangle the effects of age and size on xylem phenology, and it challenges the hypothesis that the timings and dynamics of xylem growth are size-dependent. Intra-annual dynamics of xylem formation were monitored weekly during the growing seasons 2013 and 2014 in Chinese pine (Pinus tabulaeformis) and Qilian juniper (Juniperus przewalskii) with different sizes and ages in a semi-arid region of northwestern China. Cell differentiation started three weeks earlier in 2013 and terminated one week later in 2014 in small-young pines than in big-old pines. However, differences in the timings of growth reactivation disappeared when comparing the junipers with different sizes but similar age. Overall, 77 days were required for xylem differentiation to take place, but timings were shorter for older trees, which also exhibited smaller cell production. Results from this study suggest that tree age does play an important role in timings and duration of growth. The effect of age should also be considered to perform reliable responses of trees to climate.